Evaluation of Readiness and Challenges of Carbon Tax Implementation in Indonesia from the Perspective of Climate Justice and Sustainable Development - PURNAMA, Ni Made Adelia; SUGIARTO, Cyntia Carolina; AINI, Rizka Firda Nur; PUTRI, Maria Esmeralda Sakura (Journal Management and Hospitality, 2024)
Global climate change triggered by increasing greenhouse gas (GHG) emissions has encouraged many countries, including Indonesia, to adopt environmentally-based fiscal policies, one of which is carbon tax. This article aims to analyze the basic concept of carbon tax, evaluate the readiness and challenges of its implementation in Indonesia, and provide policy recommendations based on international practices and national socio-economic conditions. This study uses a normative legal approach with a descriptive-analytical method based on literature studies. The results of the analysis show that although Indonesia already has a legal framework for carbon tax through the HPP Law and Presidential Regulation No. 98 of 2021, its implementation still faces technical, institutional, and social resistance challenges. Lessons learned from countries such as Sweden, Singapore, and Canada emphasize the importance of fair, gradual, and integrated policy design. Therefore, the implementation of carbon tax in Indonesia must be accompanied by a clear roadmap, strengthening of the emission monitoring system (MRV), technological incentives, and social compensation mechanisms so that this policy can function as a transformative instrument towards inclusive low-carbon development.